Manufacture of Local Microorganism (MOL) from Vegetable Waste with Nutrition Source Supply Variation - Hudha, A. Mohammad Istnaeny; GalihPurwa S., B. Galih; RikardusYohanes D. B., C.Rikardus; Kartika D, D. Rini (Tibuana, 2022)
Local Microorganisms (MOL) is a bioactivator consisting of a collection of various kinds of microorganisms that function as agents for the decomposition of organic matter. Vegetable waste is a collection of various kinds of vegetables after being sorted because they are not suitable for sale. Almost all vegetable waste will undergo lactic acid fermentation carried out by lactic acid bacteria (LAB). Lactic acid bacteria (LAB) are gram-positive bacteria, do not form spores, are catalase negative, are resistant to acidic conditions, and are facultative anaerobes. The purpose of this study was to determine the correct composition of rice washing water and granulated sugar for the highest number of microbes in MOL. MOL optimization was carried out by means of anaerobic fermentation for 14 days. The results of this study indicate that the microbes contained in MOL are Bacillus subtillus, Bacillus cereus, Lactobacillus acidophilus, Spirillum, Streptoverticillium, and Leuconostoc mesenterousdes. The highest total population of microorganisms in variations in the composition of rice washing water and sugar is in sample C1 which is 91 x 105 Colonies/100 mL in MOL vegetable waste, which is 650 mL of rice washing water and 100 grams of sugar.